2007
DOI: 10.1177/1066896907302369
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Gastric Gastrointestinal Stromal Tumor and Signet-Ring Cell Adenocarcinoma: A Case Report

Abstract: Synchronous tumors of the stomach are uncommon. We present a unique case of gastric synchronous tumors composed of signet-ring cell adenocarcinoma and gastrointestinal stromal tumor (GIST). The two tumors arose at the same site and were sharply juxtaposed without intermingling of morphologically distinct elements. Coincidence probably accounts for this occurrence, even if a common carcinogenic agent had been hypothesized. Preoperative imaging and endoscopic biopsy could lead to the suspicion of synchronous tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…Lee et al [18] reported a similar case of large GIST in which simultaneous signet ring cell carcinoma was detected by pathological examination prior to surgery. In their case, since curative resection could not be achieved because of the advanced stage of the gastric cancer including multiple peritoneal seeding, the histopathological diagnosis prior to surgery did not have an impact on their treatment strategy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Lee et al [18] reported a similar case of large GIST in which simultaneous signet ring cell carcinoma was detected by pathological examination prior to surgery. In their case, since curative resection could not be achieved because of the advanced stage of the gastric cancer including multiple peritoneal seeding, the histopathological diagnosis prior to surgery did not have an impact on their treatment strategy.…”
Section: Discussionmentioning
confidence: 95%
“…Simultaneous occurrence of adenocarcinoma and SMT has occasionally been observed and reported [13][14][15][16][17][18][19] but they usually originate at different sites within the stomach [13][14][15]17]. Although accurate incidence of collision tumors of adenocarcinoma and SMT is not yet determined, it is considered to be extremely rare and is usually reported as case reports.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We anticipate that the stomach may have been influenced by the same unknown carcinogen, resulting in simultaneous proliferation of different cell lines (epithelial and stromal cells) especially in the elderly. A potential pluripotent stem cell could also be the initial target of the carcinogen or causal influence, however, further studies are needed to clarify these possibilities (14). Maiorana et al suggested that gene mutations might underlie tumour predisposition in patients harbouring a double gastric neoplasia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Günümüze kadar GiST'lerin mide, kolon, rektum adenokarsinomlari, mide taçli yüzük hücreli karsinomu, özefagus karsinomu, safra kesesi karsinomu, pankreas karsinomu, hepatosellüler karsinom, même karsinomu, renal hücreli karsinom, prostat adenokarsinomu, endometrium adenokarsinomu, over karsinomu, akciger karsinomu, tiroid karsinomu, lenfoma, lösemi, nöroendokrin tümör, melanom ve adrenal nöroblastoma gibi farkli tümörlerle birlikteligi saptanmiçtir (13)(14)(15)(16). Ek olarak 2010 yilinda Soyuer ve ark.…”
Section: Olgu Sunumuunclassified